162k views
0 votes
Solve by substitution x-7y=7 6x-7y=-28

User Poushy
by
6.1k points

1 Answer

1 vote

Answer:

(-7, -2)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define systems

x - 7y = 7

6x - 7y = -28

Step 2: Rewrite systems

x = 7y + 7

6x - 7y = -28

Step 3: Solve for y

  1. Substitute: 6(7y + 7) - 7y = -28
  2. Distribute 6: 42y + 42 - 7y = -28
  3. Combine like terms: 35y + 42 = -28
  4. Isolate y term: 35y = -70
  5. Isolate y: y = -2

Step 4: Solve for x

  1. Define original equation: x - 7y = 7
  2. Substitute in y: x - 7(-2) = 7
  3. Multiply: x + 14 = 7
  4. Isolate x: x = -7

And we have our answer!

User Tarun Kolla
by
5.8k points